Mobile phone dependence among Chinese university students: the contribution of irrational beliefs and solitude - Kuang, Xiaoxue; Kennedy, Kerry John; Li, Hui (Frontiers in Psychology, 2024)
This research aimed to explore the impact of selected psychological variables on mobile phone dependence among Chinese university students. Specifically, the study focused on the relationship between solitude and irrational beliefs on mobile phone dependence. The study included 2888 university students from Guangdong, Southern China, and found that both irrational beliefs and solitude had significant direct effects on mobile phone dependence. The study also revealed that solitude mediated the relationship between irrational beliefs and mobile phone dependence. The results of this study indicate that psychosocial environments, including feelings of solitude and irrational beliefs, can influence mobile phone dependence among undergraduate students. Therefore, it is important to pay attention to these factors and their potential impact on student behaviour, particularly when it comes to academic growth and development. Further research in this area may help identify effective strategies to address mobile phone dependence among university students and promote healthier psychosocial environments.